Socio-cultural Practice: A Case Study on Personal Hygienic Behavior in the Hindu Society - Bista, Chandra Bhakta (Patan Pragya, 2023)
Hindu culture and religion has its own idea regarding what constitutes excellent physical, mental, and spiritual purity. It would be interesting to learn more about whether or not the Hindu society of today adheres to the same practices. All Hindus view maintaining personal hygiene, including cleanliness of the body, hands, clothes, hygienic toilet, and menstrual hygiene management, as a duty and a fundamental principle. Personal hygiene is considered to be a key component of Hindu society. The major objective is to comprehend the level of awareness and personal hygienic behavior in Hindu society. The study primarily takes into account two cultural and social aspects of personal hygiene. The study used hand washing behaviors, trimming and combing procedures, menstrual hygiene management, usage of safe toilet, brushing, bathing, and cleaning practices as the main areas of the study. The necessity of hygienic habits for happiness, social status, and cultural continuity was also well understood in Hindu society. More Hindus now practice personal hygiene than during the Vedic Hindu era. Hygiene habits may be improved by affecting the attitudes of the society. A social and behavior change communication approach for hygiene behaviors should be implemented by the society. The improvement of daily personal hygiene routines and behavior adjustment are required to raise a better social status and cultural practices. The Hindu community is also adopting a novel viewpoint on the connection between personal hygiene and Hindu culture.